Cutaneous polyarteritis nodosa - María Alejandra Matteoda; Paola Cecilia Stefano; Marcela Bocián; María Marta Katsicas; Josefina Sala; Andrea Bettina Cervini (Sociedade Brasileira de Dermatologia, 2015)
AbstractPolyarteritis nodosa is a rare vasculitis in children characterized by necrotizing inflammation in small and medium size arteries. It is classified into systemic and cutaneous PAN according to the presence of systemic symptoms or visceral involvement. We describe the case of a 14-year-old girl with cutaneous Polyarteritis nodosa with an atypical clinical presentation.